Reservoir Characterization of Ngrayong Formation, Sandstone with Carbonate Intercalation, Using a Geostatistical Approach Based on Petrophysical Parameters, Northeast Java Basin, Indonesia - Handoyo, Handoyo; Ronlei, Bernard Cavin; Wibowo, Andy Setyo; Sigalingging, Asido Saputra; Nathania, Edlyn Yoadan; Fatkhan, Fatkhan; Erdi, Aurio; Avseth, Per; Carbonell, Ramon; Nugroho, Pranowo; Bayu Pandito, Riky Hendrawan; Nasibov, Aladin; Ali Husein, Abdullah Ali (Testing Center for Oil and Gas LEMIGAS, 2025)
Hydrocarbons have a vital role as a driver of the global economy, which causes demand to continue to increase. To achieve production targets, oil and gas companies try to conduct exploration using efficient and accurate methods to obtain optimal hydrocarbon reserves. One approach in hydrocarbon exploration is to use geostatistical analysis to understand the characteristics of petrophysical parameters of reservoir rocks (e.g. porosity, permeability, water saturation and facies). This study aims to characterize reservoirs in the NE Java Basin using a geostatistical approach that Sequential Gaussian Simulation (SGSIM) to produce random realizations that can be adjusted and validated through geostatistical analysis of data before and after the simulation. The dataset used in this study consist of well data, seismic line, and core data. The results shows the petrophysical properties distribution from the simulation reveals the dominance of carbonate sandstone reservoirs in the central part of the study area with a thinning slope towards the northwest and southeast, while sandstone reservoirs are only dominant in the southeast direction of the study area. This research provides important insights in understanding reservoir characteristics and can be a basis for efficient decision making in the exploration of hydrocarbon resources in this area.